Metabolism and epigenetics in cancer: toward personalized treatment - Zhang, Xiaoman; Liu, Dequan; Yin, Sulan; Gao, Yaru; Li, Xiaorui; Wu, Guangzhen (Frontiers in Endocrinology, 2025)
Epigenetic changes, such as DNA methylation, chromatin remodeling, and histone modifications, regulate gene expression without altering the DNA sequence. This review systematically analyzed over 500 studies including human cell line experiments (n>200), animal models (n>50), clinical cohort studies (n>100), and bioinformatics analyses retrieved from PubMed, Web of Science, and TCGA (The Cancer Genome Atlas). Studies increasingly show that genes involved in glucose and lipid metabolism, energy production, and modulation of metabolic hormones are regulated through epigenetic mechanisms. On the other hand, various metabolites participate in epigenetic modifications as coenzymes or substrates. Therefore, a greater understanding of the crosstalk between metabolism and epigenetics in cancer-related pathways could lead to the identification of key signaling molecules for targeted therapies, and raise the possibility of using dietary interventions to modulate epigenetic markers for individualized treatment. In this review, we have summarized the metabolic and epigenetic regulatory networks in cancer development, including glycolipid metabolic reprograming, the role of metabolites produced by the glut flora and tumor microenvironment, and key epigenetic drivers such as non-coding RNAs (ncRNAs). Data were curated from peer-reviewed articles, grounded in mechanistic studies using cell lines (SW480, MCF7 (Michigan cancer foundation-7)) and animal models (APC-mutant mice), with a focus on mechanistic studies, omics analyses, and translational research. Furthermore, we have discussed the potential of therapeutically targeting these pathways, along with the current challenges and future research directions, and a new strategy for reversing therapeutic drug resistance based on metabolism and epigenetic interaction was systematically explored.